115k views
5 votes
If x-1=3y, then what is (6y+2)^2

1 Answer

4 votes

Answer:

(6y + 2)² = 4x²

Explanation:

Given: x - 1 = 3y

Dividing by 3,

⇒ y =
$ (x - 1)/(3) $

Now, to determine 6y, multiply the equation throughout by 6y.

⇒ 6y =
$ (6(x - 1))/(3) $

⇒ 6y = 2(x - 1)

⇒ 6y = 2x - 2

Now, for 6y + 2, add 2 on both sides.

⇒ 6y + 2 = 2x - 2 + 2

6y + 2 = 2x

Finally, Squaring both sides, will give us (6y + 2)².

⇒ (6y + 2)² = (2x)²

= 4x² which is the required answer.

User Dave Durbin
by
5.2k points